P495 Vedolizumab trough concentrations and histological remission in Ulcerative Colitis: Results from the LOVE-UC study. (30th January 2023) - Hanzel, J; Baert, F; Löwenberg, M; Ferrante, M; Bossuyt, P; Hoentjen, F; Franchimont, D; Palatka, K; Peeters, H; Mookhoek, A; de Hertogh, G; Clasquin, E; et al.
Abstract: Background: To date, the association between vedolizumab (VDZ) serum concentrations and histological remission in ulcerative colitis (UC) has not been studied prospectively. VDZ serum concentrations could potentially offer additional guidance for predicting histological remission. We studied the relationship between VDZ serum concentrations and histological remission in a prospective study. Methods: LOVE-UC was a multicentre international (Belgium, the Netherlands, and Hungary) open label prospective study in patients with moderately to severely active UC treated with VDZ. VDZ serum concentrations were measured at trough prior to every infusion. Endoscopy was performed at baseline, week 26 and 52. Biopsies from the most severely affected area and endoscopy videos were scored by blinded central readers. Histological remission was defined as a Robarts Histopathology Index <3 without neutrophils. Patients who did not undergo histological assessment were regarded as not having reached histological remission. Endoscopic remission was defined as a Mayo endoscopic sub-score 0. Results: A total of 121 patients (61 male, 62 with prior exposure to tumour necrosis factor antagonists, mean total Mayo score at baseline of 9) received at least one infusion of VDZ. At week 26, 37.2% (45/121) patients were in histological remission, 38.8% (47/121) were in histological remission at week 52. The corresponding rates of combined histological and endoscopic remission were 19.8% (24/121) and 20.7% (25/121), respectively. Median VDZ serum concentrations were numerically higher at all time points in patients who achieved histological remission at week 26 than in those who did not (Table 1). Concentration thresholds (sensitivity, specificity, positive predictive value, negative predictive value, area under the receiver operating characteristic curve) of 32.5 mg/L (66%, 68%, 54%, 74%, 0.681) at week 6 and 12.5 mg/L (76%, 60%, 61%, 70%, 0.724) at week 22 were associated with histological remission at week 26. Higher proportions of patients achieved histological remission at week 26 in higher VDZ serum concentration quartiles (Figure 1). Conclusion: VDZ serum concentrations were positively associated with histological remission in UC, although the predictive value of serum concentrations for subsequent histological remission was modest.